2016
DOI: 10.1016/j.jamda.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Apathy and Its Response to Antipsychotic Review and Nonpharmacological Interventions in People With Dementia Living in Nursing Homes: WHELD, a Factorial Cluster Randomized Controlled Trial

Abstract: Antipsychotic review can play a significant role in improving apathy in people with dementia living in nursing homes, when combined with psychosocial interventions such as social interaction and exercise. Guidance must be adapted to reflect this subtlety in care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In the study by Manera et al, participants reported a preference for the virtual reality (VR) condition vs the paper condition, even if the task was more difficult. In a cluster RCT by Rajkumar et al, antipsychotic review in combination with either social interaction or exercise significantly reduced NPI‐NH apathy scores in demented patients living in nursing homes. In the pilot RCT by Sanchez et al, a positive effect was observed on neuropsychiatric symptoms and dementia severity in the MSS environment (MSSE) treatment vs the activity group.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the study by Manera et al, participants reported a preference for the virtual reality (VR) condition vs the paper condition, even if the task was more difficult. In a cluster RCT by Rajkumar et al, antipsychotic review in combination with either social interaction or exercise significantly reduced NPI‐NH apathy scores in demented patients living in nursing homes. In the pilot RCT by Sanchez et al, a positive effect was observed on neuropsychiatric symptoms and dementia severity in the MSS environment (MSSE) treatment vs the activity group.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, Treusch et al suggested that the use of physical activation and biography‐orientated mobilization could motivate demented patients. Moreover, Brodaty and Burns propose that individually provided therapeutic activities may have the best available evidence for effectiveness in dementia. Additionally, education is necessary to assist families in understanding apathy, as apathetic patients are often characterized lazy or oppositional …”
Section: Discussionmentioning
confidence: 99%
“…Fifteen of seventeen studies of tailored activity and eight of the nine studies using non-tailored activity reported a positive or partly positive outcome (481). In the Improving Well-being and Health for People with Dementia (WHELD) study, antipsychotic review combined with social activity or exercise led to a reduction in apathy as a secondary outcome (482). The ADMET (Alzheimer's Disease Methylphenidate Trial) with 60 people given 20 mg methylphenidate or placebo found no difference in the apathy evaluation scale but more people in the intervention group rated as mildly to markedly improved (483) Therefore, although there are no definitive trials on management of apathy, there is an indication that interventions that increase activity or methylphenidate may be helpful.…”
Section: Apathymentioning
confidence: 99%
“…Prevailing evidence does not support the use of antipsychotic medications for treating apathy in PD, but stopping long-term antipsychotic medication may lead to worsening of apathy [166].…”
Section: Managementmentioning
confidence: 99%